EFFECT OF GARLIC (ALLIUM SATIVUM) AND GINGER (ZINGIBER OFFICINALE) AS FEED ADDITIVES ON BLOOD PROFILE AND BROILER PERFORMANCE - Karangiya, VA; Sasvani, HH; Padodara, RJ; Ribadiya, NK; Ribadiya, SJ (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was undertaken to investigate the effect of incorporating garlic and ginger powder, as a growth promoter in broiler feed . 240 day-old commercial broiler chicks (Cobb-400) were divided equally into four groups of 60 birds each, and were assigned to four isocaloric isonutritive diets, viz., Diet-I basal control diet without additives, Diet-II, basal diet + 1 % garlic, Diet-III, basal diet + 1 % ginger and Diet-IV, basal diet + mixture of 1 % garlic and 1 % ginger. The experiment was conducted in three replicates each of 20 birds. Feed and water were offered ad libitum . The starter and finisher diets were given to birds from 1 to 28 and 29 to 42 days of age, respectively. Growth performance parameters and blood parameters were measured. Broilers fed Diet - IV had significantly (P
Keywords: Garlic and Ginger; Broiler Performance; Haematology